Ameliorating Metabolic Profiles After Kidney Transplantation: A Protocol for an Open-Label, Prospective, Randomized, 3-Arm, Controlled Trial - Yin, Saifu; Ma, Ming; Huang, Zhongli; Fan, Yu; Wang, Xianding; Song, Turun; Lin, Tao (Frontiers in Medicine, 2021)
Aim: High prevalence of metabolic disorders causes higher risk of cardiovascular diseases after kidney transplantation (KT), which remains the main burden impairing short-term and long-term survival. This open-label, prospective, randomized, 3-arm, controlled trial will evaluate the safety, tolerability and efficacy of metformin and empagliflozin in ameliorating metabolic profiles after KT. Methods: After a screening assessment, eligible patients with an estimated glomerular filtration rate (eGFR) >45 mL/min/1.73m2 are randomly assigned to standard triple immunosuppression alone, standard immunosuppression plus metformin (500 mg twice daily), standard immunosuppression plus empagliflozin (25 mg once daily) from discharge. The primary endpoint is the differences in the visceral-to-subcutaneous fat area ratio over 12 months, evaluated by magnetic resonance imaging (MRI). Secondary outcomes include kidney graft function, glycometabolism, lipid metabolism, and inflammatory parameters. The trial will enroll 105 kidney transplant recipients, providing 90% power to detect the difference at 5% significance.